Thermal Design of Microreactor Structural Elements for Water Quality Analyser. (April 2020) - Matviykiv, O; Klymkovych, T; Farmaha, I; Bokla, N; Marikutsa, U; Pytel, K
Abstract: The research object is a Lab-chip device for environmental water quality monitoring. The main objective of the actual work is to determine a set of functional, geometric and technological parameters of Lab-chip microreactor to provide optimal temperature field conditions for predefined chemical reaction protocols. Since Lab-chip operates with a microdose of liquids or reagents and temperature processes in fluid flows are highly inertial, the problem of setting, maintaining and ensuring fast transient of certain temperature values in different areas of Lab-chip microchannels is nontrivial. The main focus was pointed on precise heating of defined Lab-chip areas (reaction chambers) and strict compliance with the non-stationary thermal regime, required for chemical reaction protocols. Modelling and simulation were done in COMSOL Multiphysics tool. As a result of the conducted research, there was obtained a set of parameters that provides the required thermal regime of reaction microchamber for the physicochemical determination of selected hazardous species in environmental water samples.